A good place to do business the politics of downtown renewal since 1945 - Biles, Roger, 1950-; Rose, Mark H., 1942- (Urban life, landscape, and policy., 2022)
"This book looks at the politics of downtown business promotion as an urban renewal strategy from the end of World War II to the present, with a focus on five case cities: Philadelphia, Chicago, Detroit, St. Louis, and Cleveland"--